The analysis of thermal calculation for air stove drying system - Li Jun; Li Xue (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
This article discusses the existing calculation of heat for a coal-fired hot-blast furnace. By utilizing the standard method of heat calculation for boilers, considering the relation between the theoretical combustion temperature and the excess air coefficient of the boiler, combining some operational parameters of a coal-fired powder hot-blast furnace, the heat calculation of iron ore concentrating dry combustion on a coal-fired hot stove is discussed. It is used to prevent coke and optimize combustion. It also discusses the advantages and disadvantages of flue gas recirculation systems. The conclusion will show the practical applications of this. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.857